2021
DOI: 10.1093/molbev/msab017
|View full text |Cite|
|
Sign up to set email alerts
|

Bridging Themes: Short Protein Segments Found in Different Architectures

Abstract: The vast majority of theoretically possible polypeptide chains do not fold, let alone confer function. Hence, protein evolution from preexisting building blocks has clear potential advantages over ab initio emergence from random sequences. In support of this view, sequence similarities between different proteins is generally indicative of common ancestry, and we collectively refer to such homologous sequences as ‘themes’. At the domain level, sequence homology is routinely detected. However, short themes which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 94 publications
(153 reference statements)
1
83
0
Order By: Relevance
“…AncPept , 23 the bridging themes , 27 Fuzzle 26 and our CA_motifs specify four sets of putatively ancestral protein motifs. AncPept , the bridging themes , and Fuzzle recruit motifs from pairwise alignments of HMMs representing SCOP domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AncPept , 23 the bridging themes , 27 Fuzzle 26 and our CA_motifs specify four sets of putatively ancestral protein motifs. AncPept , the bridging themes , and Fuzzle recruit motifs from pairwise alignments of HMMs representing SCOP domains.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of AncPept and CA_motifs , the cut‐off values were 0.5 and 0.55, respectively. In the set of the bridging themes , 30% have a TM‐score < 0.3 and only 25% a score > 0.5 27 . For the identification of Fuzzle motifs, a TM‐score threshold of 0.3 in combination with an RMSD threshold of 3 Å and no upper or lower bound for the length of the motifs has been used 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is attractive because it effectively allows new proteins to be assembled as if they are made of molecular LEGO® building blocks. Modular design is relevant from an evolutionary perspective, as there is increasing evidence that natural proteins evolve from fragments or motifs, such as short propellor-like motifs that have evolved into modern β-barrels [71], an omnipresent Rossman ribose-binding motif that hints at common ancestry among Rossman-fold enzymes that use ribose-based cofactors [72], and a β-α-β fragment that appears to be the minimal functional motif leading to modern P-loop NTPase and Rossman enzymes [73], among other examples [74][75][76]. Therefore, modular design mimics the repeating themes that lead to the natural evolution of functional protein scaffolds.…”
Section: Enzyme Engineering From Protein Lego®mentioning
confidence: 99%
“…These are most commonly classified in terms of 'domains', typically comprising ~50-250 amino acids that represent an independent folding unit [84]. However, a number of studies have suggested that duplication and recombination of segments shorter than domains could have been the origin of the domains themselves and that these are therefore the ultimate building blocks [71,75,81,85,86].…”
Section: Trends In Biochemical Sciencesmentioning
confidence: 99%